Razón moral, razón política, razón ficcional: en torno a El monarca de las sombras (2017) de Javier Cercas y la ficción de archivo - Yael Natalia Tejero Yosovitch (Cuadernos LIRICO)
The novel by Spanish writer Javier Cercas, The Monarch of Shadows (2017), closes a cycle of archival fiction inaugurated by his most famous work, Soldiers of Salamis (2001). The novel reconstructs the life of Cercas's great-uncle, Manuel Mena, a Falangist soldier fallen in the Battle of the Ebro, during the Spanish Civil War. This article aims to analyze the way in which the web of documents that makes up the archival fiction of The Monarch of Shadows is constructed through the constitution of two types of narrators that are postulated as opposites: one would represent the fictional narrator and the other, the historian narrator. We argue that from a triadic conception that distinguishes history, fiction and myth, there is an inversion of the domain of each type of narrator, being the historian narrator the one who fictionalizes through conjecture and the literary narrator the one who dismantles the documentary device.